Desain Realistic Mathematics Education Integrasi Tradisi Peresean Masyarakat Lombok pada Materi Kombinasi - Supiarmo, M. Gunawan; Primajati, Gilang; Ruslin, Ruslin (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Mathematics learning is often considered abstract and less relevant to real life, making it difficult for students to understand the concept. Realistic Mathematics Education (RME) offers an approach that helps students build understanding through real situations. The Peresean tradition with its competition structure and cultural values ​​has the potential to be a concrete and meaningful combination learning context. This study aims to design a realistic mathematics learning design that integrates the Peresean tradition into a combination of materials at the Senior High School level. The main problem behind this study is the low understanding of students towards the combination concept due to the delivery of material that is too abstract and has minimal relevance to real life. The RME approach offers a solution through the use of the real context of the Peresean Tradition which was chosen because it has a competition structure that has the potential to be mathematically modeled in the combination context, such as selecting opponents or compiling match schemes. This study uses a qualitative approach with the type of design research in the development studies category. The research process is limited to the preliminary design stage, which includes context analysis, literature studies, and the development of learning designs. The research results are in the form of a theoretical and contextual culture-based learning design, which is validated reflectively based on RME principles and suitability to the curriculum.